Características organolépticas de la carne de pavo americano big-6 con dieta alimenticia balanceado + nabo (brassica rapa). - Arévalo Briones, Wellington Manuel (2015)
The practical project complexivo examination was conducted at the Experimental Farm "La María", owned by the State Technical University of Quevedo (UTEQ), specifically in Poultry Program, located at km. 7½ via the Quevedo - El Empalme. The overall objective of this study was to evaluate the organoleptic characteristics of meat turkey BIG-6 American diet (balanced + turnip) to improve production and get better quality meat. The fieldwork lasted 15 days included from 9 until 22 December 2014; corresponding to the beginning and end of phase feeding balanced diet + turnip and the respective slaughter; and December 23, 2014 upon completion of the investigation tasting samples to assess the organoleptic characteristics of the turkey with a group of academics at the institution. Importantly was maintained at 50 American turkeys BIG-6 unsexed with balanced + turnip treatment, which received the same power, space and management. Besides the statistical design Chi Square two treatments with 5,000 g was used. turkey breast each, with organoleptic characteristics such as variable evaluated. The assessment of organoleptic characteristics to determine the quality of the meat was made in 14 days after nutritional supplementation balanced + turnip and these are: taste, smell, color and juiciness. The results of the investigation determined that the sensory characteristics with greater influence on the acceptance of turkey meat by consumers are flavored with a value of chi (86,10), odor with a value of chi (100) and juiciness with a value of chi (32.57), knowing ……